Guide to quality control - Ishikawa, Kaoru (Asian Productivity Organization, 1976)
This classic, hands-on guide, written by one of the most widely respected masters of quality, teaches the fundamental tools of quality, including: Data collection, Control charts, Histograms,.. This best-selling text has been used extensively by schools and major U.S. companies for training students, supervisors, and line personnel. Simply written and self-teaching, it encourages workers to seek out applications of the tools in their work. Includes practice problems.